Attitude and Understanding of Concepts: It’s Influence in Science Learning - Anggraini, Lika; Maison; Syaiful (LPPM Undiksha, 2022)
Attitude measurement is very important because the teacher can find out that each student responds to science learning with an indication that students reject or accept science learning in students. This research is aimed to analyse how the science attitude of students, analyse understanding of students' concepts on Newton's law material and analyse the effect of science attitudes on students' understanding of concepts in Newton's law material. This research is a mixed type of research, namely a mixed method with the aim of knowing how science attitudes are, how students understand concepts, and the effect of science attitudes on students' conceptual understanding. This study took a sample of 358 junior high school students with the sampling technique used was purposive sampling. The instruments used were student science attitude questionnaires, concept understanding questionnaires, and interview sheets. Analysis of the data used in the form of descriptive statistics, simple linear regression, and Miles Huberman for qualitative data. The results obtained from the study are that the overall average of students is in a good category on both variables, it is also known that there is an influence of 51.2% of the influence of students' science attitudes on students' understanding of concepts. This certainly illustrates that junior high school students in the Telaipura sub-district are quite good at understanding Newton's law concepts.